2019
DOI: 10.1123/jpah.2018-0703
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Methods for Assessing Compliance With a Physical Activity Guideline for Children in Preschools

Abstract: Background: According to the US Institute of Medicine guideline, preschool-aged children should participate in ≥15 minutes of physical activity (PA) per hour or 3 hours per day over 12 hours. Examinations of PA guideline compliance to date averaged time spent in PA over several days; however, children could exceed the guideline on some days and not on others. Therefore, this cross-sectional study examined PA guideline compliance in preschool children based on number of minutes per hour (average method) and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Findings generated from the International Children's Accelerometry Database suggest that seasons and weather have a greater effect on PA in preschool-aged children than that in older children and adolescents (16). In a previous observation of PA in preschoolers with no intervention in place, we found no significant differences in total amounts of PA and MVPA, nor the percentage of days the PA guideline was met between two different seasons (autumn and winter) (10). In the current study, variation in PA was observed over the course of a school year across the fall, winter, and spring seasons.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Findings generated from the International Children's Accelerometry Database suggest that seasons and weather have a greater effect on PA in preschool-aged children than that in older children and adolescents (16). In a previous observation of PA in preschoolers with no intervention in place, we found no significant differences in total amounts of PA and MVPA, nor the percentage of days the PA guideline was met between two different seasons (autumn and winter) (10). In the current study, variation in PA was observed over the course of a school year across the fall, winter, and spring seasons.…”
Section: Discussioncontrasting
confidence: 65%
“…To examine the extent to which each child was in compliance with the IOM guideline on a daily basis, PA was considered to be compliant with the guideline if a participant was active, on average, for ≥15 min•h −1 on a given day. For each child, the number of days in compliance was divided by the total valid accelerometer days to yield the percentage of days in compliance with the guideline (10).…”
Section: Assessment Of Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, PA is a potentially low‐cost method of addressing a range of behavioral (and health) risks, yet it is widely underutilized. Although many preschools incorporate free play and outdoor time into their schedules, recent work shows that only 62% of preschool children studied met the recommended guideline of 15 min/hr of PA on a daily basis (Tompkins et al, 2019). Thus, a structured and systematic approach, such as implementation of a PA program like Kiddie CATs on the Move , may be necessary to provide children with adequate levels of PA.…”
Section: Discussionmentioning
confidence: 99%
“…However, most published evidence has been generated in traditional PE classes, whereas little research has examined the ecological correlates of PA and SB in sessions guided by the principles of experiential psychomotricity. Despite studies showing low levels of PA and high levels of SB in ECE settings (De Craemer et al, 2018; Pate et al, 2004; Pereira et al, 2019; Tompkins et al, 2019; World Health Organization, 2019), movement sessions based on the principles of experiential psychomotricity have not been studied through accelerometry and direct observation in our country or in other countries in Europe. Even though accelerometry may be the objective measure of choice for evaluating young children’s PA (Chow et al, 2015; Van Cauwenberghe et al, 2012), this method alone could be insufficient for exploring the particular social patterns of PA correlates (McKenzie and van der Mars, 2015).…”
Section: Introductionmentioning
confidence: 99%